Enhancing fertility at early ages in heifers by supplementing critical nutrients of reproduction - Arangasamy, A; Pal, D T; Devi, Letha; Niketha, L; Mech, A; Senani, S; Kataktalware, M A; Reddy, G B M; Giridhar, K; Bhatta, Raghavendra (Indian Farming, 2022)
This study was aimed to advance the pregnancy and conception in heifer, repeat breeder and anoestrus cow. ICAR-NIANP critical nutrient formulation with combination of vitamins and Tonophosphan along with deworming was attempted. In overall 75% animals(15/20) conceived in treated group compared to 23% animals (03/13) in control group within 90 days of treatment period. The repeat breeder and anoestrus dairy cows responded very well to the above mentioned treatment protocol and 79.24% of repeat breedercows (42/53) and 80.76% of anoestrus animals (21/26) conceived, respectively. Supplementation of trace mineral has been shown to enhance fertility in cattle, possibly by reducing embryo death. The practice of combined treatment for early pregnancy in heifer andconception of repeat breeder and anoestrus cow with critical minerals, vitamins and Tonophosphan along with deworming schedule has improved the fertility with minimum treatment cost.